Love, Marriage, and Jewish Families : Paradoxes of a Social Revolution - Fishman, Sylvia Barack, 1942- (Book collections on Project MUSE., 2015)
Illustrates the complex and diverse ways that Jews in the United States and Israel are reshaping dating, marriage, and family life-with some surprising consequences.